The Gene Illusion : Genetic Research in Psychiatry and Psychology Under the Microscope. - Joseph, Jay (Algora Pub., 2007)
Genetic factors are increasingly presented as an important influence on psychiatric disorders, personality, intelligence, and various types of socially unacceptable behavior? as if that were an unassailable fact, proven by research. Jay Joseph?s timely.